Влияние гордокса на локальное кровообращение в стенке кишечника в условиях моделирования последовательно увеличивающейся интраабдоминальной гипертензии - Сапегин, В.И. (Таврический медико-биологический вестник, 2014)
В гострих експериментах на кроликах вивчено захистну дiю гордоксу (10000 ОД/кг в/в одноразово)
на змiни кровообiгу, його регуляцiї та кисневого балансу у тканинах кишечника при послiдовному
моделюваннi стандартних рiвнiв интраабдомiнальної гiпертензiї (IАГ) – 50, 100, 150, 200, 250, 300, 350
мм водного стовбчику за допомогою стенду нашої конструкцiї. На тлi вказаних рiвнiв IАГ вивчено локальий
кровотiк (КТ), дилататорну (КрСО₂) та констрикторну (КрО₂) реактивнiсть судин методом клiренсу водню,
а також напругу кисню у тканинах (рО₂) стiнки кишечнику методом полярографiї за допомогою спецiальних
електродних блокiв. Пiд впливом усiх модельованих рiвнiв IАГ вiдбувається уповiльнення КТ, пригнiчення
КрСО₂ та, ще бiльше, КрО₂, а також зниження рО₂ у тканинах. Зiставлення швидкостi розвитку вказаних
зрушень свiдчить про розвиток оборотного iшемiчного ураження при 1 – 2 ступенях синдрому
iнтраабдомiнальної гiпертензiї, а при 3 – 4 ступенях – про прогностично несприятливi змiни, що ставлять
пiд сумнiв подальше виживання кишечнику. Гордокс у вищевказаных умовах погiршує кровообiг та кисневий
баланс тканин кишечнику, але пiдвищує життєздатнiсть тканин в умовах iшемiї. Тому гордокс не може
бути рекомендован хворим на IАГ. In acute experiments on rabbits with modeling by our designed stand of sequential increasing standard
levels of intra-abdominal hypertension (IAH) – 50, 100, 150, 200, 250, 300, 350 mm H₂O the protective effect
gordox (10,000 units / kg / single dose) upon the changes in blood circulation, its regulation and oxygen balance
in the intestinal tissues were studied. The local blood flow (BF), dilatation (KrCO₂) and constriction (KrO₂)
vascular reactivity by hydrogen clearance method and tissue oxygen tension (pO₂) in the intestinal wall tissues
by polarographic method using special own designed electrode units on the background of these IAH levels
were studied. Under the influence of simulated IAH levels slowing of BF, oppression of KrCO₂ and even more
KrO₂, and reduction of pO₂ in tissues is observed. Comparison of the rate of development of this shift suggests
the development of reversible ischemic injury at 1 – 2 degree of Abdominal Compartment Syndrome, and at 3 –
4 degree about prognostically unfavorable changes questioning the continued survival of the intestine. Gordox
worsens circulation and intestinal tissue oxygen balance, but enhances the viability of the tissues under ischemia
in the aforecited conditions. In connection with it gordox can not be recommended for patients with IAH.